PEMBELAJARAN PENJASORKES MELALUI MEDIA BERMAIN BOLA KERANJANG TERHADAP HASIL BELAJAR SISWA SDLB-C TUNA GRAHITA (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The  problem  in  this  study  is  whether  there  is  an  increase  in  Penjasorkes  learningoutcomes  through  media  play  basket  ball  for  mentally  students  disabled  SDLB-CEducation  Foundation  Exceptional  Demak?. This  study  aims  to  improve  learn-ingoutcomes  through  the  Penjasorkes  media  play  basket  ball   for  students  learningSDLB-C  in  Physical  Education,  Sport  and  Health.  This  study  uses  classroomaction  research.  In  the  implementation  of  the  first   cycle  and  second  cycle  ofmeetings  held  1  meeting,  where  each  cycle  has  shown  an  increase  Penjasorkeslearning  outcomes  and  meet  the  completeness  criteria  are  minimal  so  it  does  notneed  to  be  held  next  cycle.  Based  on  the  results,  the  results  of  the  percentage  ofcompletion  on  the  first  cycle  that  can  meet  the  KKM  is  equal   to  52.94%  of   thetotal  number  of  students  in  the  second  cycle  and  increased  to  88.23%  of  the  totalnumber  of  students.  Based  on  the  above  results,  it  can  be  concluded  that  thePenjasorkes  learning  using  media  play  basket  ball   can  improve  the  process  inimproving  learning  outcomes  for  mentally  disabled  students  SDLB-C  EducationFoundation  Exceptional  Demak.  Expected  for  Penjasorkes  teachers  in  SDLB-Ccan  use  the media  playing  basket  ball  in  the  learning of  Physical  Education,  Sportand Health, as an alternative to implement-ing the learning.